Study for differences in jumping when volleyball players wear multiple competition shoes - Hara, Y.; Ozawa, Y.; Fujii, M.; Ozawa, S.; Yamada, H. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Volleyball players perform jump lots times in the game. Therefore, volleyball shoes (VS) are designed with emphasis on functionality such as cushioning, flexibility, and grip. For basketball shoes (BS), Brizuela et al. (1997) have suggested that increasing ankle support in vertical jumps leads to an increase in impact load upon landing and a decrease in performance. However, multiple competitions shoes have not been compared. The purpose of present study was to examine the effects of differences in multiple competition shoes on jumping performance. METHODS: Subjects were 15 top-level Japanese college male volleyball players (180.6±6.9 cm, 72.3±4.1 kg, 20.7±1.3 years old). The group that usually practices with the VS (VSU group) had 8 subjects, and the group that usually practices with the BS (BSU group) had 7 subjects. They wore VS (ROTE JAPAN LYTE FF 3, ASICS, Japan), BS (GLIDE NOVE FF 3, ASICS, Japan) and control shoes (CS, school slippers, Achilles, Japan), and performed spike jumps on a force plate. The subjects performed a jump with a one-step run-up (one-step run-up jump) and a jump with a free run-up (free run-up jump). Jumping height (JH) were measured using a yardstick (Yardstick, S*C CORPORATION, Japan). Ground reaction force was captured using four force plates. The ground reaction force (GRF) of volleyball and basketball shoes were normalized by that of control shoes for excluding the effects of body weight and jumping height (nGRF). The obtained JH and GRF were compared between groups. One-way ANOVA was used for comparisons among VS, BS, and CS. T-test was used to compare VS and BS normalized by CS. RESULTS: In free run-up jumps and single run-up jumps, there was no significant difference in jump height (cm) between the VSU and BSU groups when wearing the three shoes (VS, BS, CS). In the free run-up jump, there was no significant difference in the GRF during the landing phase between the VSU group and the BSU group when wearing the three shoes. However, in the BSU group for one-step approach jump, the GRF during the landing phase when wearing CS was significantly higher than that when wearing VS (p=0.001) and when wearing BS (p=0.02). In the BSU group during a one-step approach jump, nGRF during the landing phase when wearing VS was significantly lower than when wearing BS (p=0.008). On the other hand, in the VSU group during one-step approach jumps, nGRF during the landing phase when wearing VS showed a higher value compared to when wearing BS (p=0.016). CONCLUSION: The results of this study can be attributed to the fact that VS and BS are primarily designed to prevent jumping injuries. Furthermore, it was suggested that both the VSU and BSU groups may use different strategies to control their jumps when wearing shoes that they do not normally use. The results of this study revealed that differences in multiple competition shoes have various effects on jumping performance.